Prevalence of Metabolic Syndrome and Insulin Resistance in a Sample of Adult ADHD Outpatients - di Girolamo, Giulia; Bracco, Irene Francesca; Portigliatti Pomeri, Alberto; Puglisi, Soraya; Oliva, Francesco (Frontiers in Psychiatry, 2022)
Background High prevalence of Metabolic Syndrome (MS) was found in patients with schizophrenia and bipolar disorders. Insulin Resistance (IR) seems to mediate MS role in developing cardiometabolic consequences. Aims To investigate the prevalence of MS, and the role of MS components and IR surrogate indexes in determining MS in adult ADHD outpatients. Methods In the present cross-sectional study, MS, defined according to the Expert Panel on Detection, Evaluation and Treatment of High Blood Cholesterol in Adults (ATP III), and IR surrogate indexes were assessed on a consecutive sample of adult ADHD outpatients. Logistic regression analysis was performed to evaluate the effect of each ATP III component and IR surrogate index in determining MS. Results Seventeen out of 158 patients (10.8%, 95%CI = 0.064/0.167) fulfilled the ATP-III criteria for MS. A comprehensive comparison with prevalence in the reference population was hindered by the lack of patients over 60 in the study sample, however under this age no significant differences were found. Among MS components, blood triglycerides level (OR = 1.02, 95%CI=1.01/1.03, p = 0.001) was the main predictor for MS, followed by diastolic blood pressure (OR = 1.08, 95%CI=1.01/1.16, p = 0.024) and waist circumference (OR = 1.06, 95%CI=1.01/1.13, p = 0.029). Lipid Accumulation Product (LAP, OR = 1.0006, 95%CI=1.0003/1.0009, p < 0.001) outperformed Triglyceride-Waist Circumference (TG-WC, OR=1.03, 95%CI=1.01/1.04, p < 0.001) in predicting MS. Conclusions More attention should be paid not only to MS but also to each ATP III component of MS and LAP in ADHD patients both at first assessment and during follow-up process.